Lathyrus genetic resources network: Proceedings of a IPGRI-ICARDA-ICAR Regional Working Group Meeting, 8-10 December 1997, New Delhi, India - Mathur, P.N.; Ramanatha Rao, V.; Arora, R.K.; International Plant Genetic Resources Institute (1999)
Neglected and underutilized crops ”have received relatively less attention in national or international priorities. IPGRI has recognized the potential importance of such crops, and in partnership with others around the world, has undertaken a series of activities to understand and promote the role of such crops in helping to achieve food security and agricultural sustainability through local peoples” maintenance of diversity and in realizing their potential for improvement. The potential of Lathyrus sativus (Grass pea) as a nutritious pulse with high quality grain and fodder, is well recognized in South Asia, Ethiopia and parts of Central, West and North Asia, where other species of this genepool also occur. The local types are tolerant to flood and drought conditions and possess unique adaptation as a post-rice crop across much of South Asia. Other cultivated species of Lathyrus are L. ochrus and L. cicera mainly grown in Central, West and North Africa as a fodder crop. These proceedings are the outcome of the first meeting of this Working Group. This meeting, which took place at NBPGR, New Delhi in December 1997, reviewed progress, reaffirmed the concern and interest of the participating countries in this crop and worked out on the modalities of the Lathyrus Genetic Resources Network (LGRN) - its proposed structure and functioning.